Pengaruh Fee Audit dan Tekanan Anggaran Waktu terhadap Kualitas Audit: Studi Kasus pada Kantor Akuntan Publik di Wilayah Semarang - Vida Indah Viratna; Merliana Saputri; Alya Sari Khanifah; Etik Yuliana; Herlina Manurung (International Forum of Researchers and Lecturers, 2024)
Auditors are tasked with evaluating and reviewing client or company financial reports. Stakeholders rely on audit reports issued by public accountants. This is what makes auditors have the responsibility to produce quality output from a series of audit processes. Stakeholders use financial reports that have gone through an audit process as a guide in the decision-making process. Auditors who face ethical problems sometimes do not make the right decisions when carrying out audit tasks. Some auditors sometimes do not carry out their duties in accordance with the professional code of ethics when facing technical situations. So until now, there are still cases related to audit costs and time budget pressures which may affect the quality of audits made by auditors. This case study aims to examine the impact of audit fees and time budget pressure on audit quality. This research involved all auditors who work at Public Accounting Firms in Semarang, with 35 auditors as samples selected using the convenience sampling method. Multiple linear regression analysis is used as an analytical tool, and the research results show empirically that audit fees and time budget pressure have a significant influence on audit quality.